Bridging the social gap: The role of the metaverse in alleviating loneliness and language barriers among international students - Cao, Huining (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the relationship between international students' use of metaverse technology during cross-cultural adaptation and their feelings of loneliness, with particular attention to the moderating role of language barriers in this relationship. Through empirical analysis of the sample data, the study found that the frequency of metaverse technology use did not significantly alleviate loneliness directly (p > 0.05). However, further moderation effect analysis indicates that the degree of language barriers plays a significant moderating role between metaverse usage and loneliness, revealing a significant interaction (p < 0.05). Specifically, the higher the language barrier, the more differentiated the pattern of the impact of metaverse usage on loneliness becomes. Furthermore, this study also finds that students of different age groups exhibit distinct differences in their acceptance of metaverse technology. Compared to other age groups, younger students aged 25–30 demonstrated higher acceptance and willingness to use the technology, potentially linked to this cohort's innate affinity and adaptability towards digital technologies. In conclusion, this study reveals complex, multi-layered connections between the application of metaverse technology, experiences of loneliness, and cross-cultural adaptation processes. It also provides preliminary insights into the psychological adaptation of international students in the digital age, from the perspective of social support systems. The study concludes by offering theoretical and practical implications, providing directional guidance for subsequent research in this field.